(3x+1)² - (x-√6)(x+√6)=(4+2x)² + 4x(x-5)
Wiem że łatwe ale nie chce mi wyjść -.-
9x²+6x+1-(x²-6)=16+16x+4x²+4x²-20x
9x²+6x+1-x²+6=16+16x+4x²+4x²-20x
8x²+6x+7=8x²-4x+16
6x+7=-4x+16
10x=9
x=0,9
9x^2 +6x+1-(x^2 - 6)=16+ 16x+4x^2 +4x^2-20
9x^2 +6x+1-x^2+6=16+16x+4x^2 +4x^2-20
8x^2+6x+7=8x^2+16x-4 /-8x^2
6x+7=16x-4 /-6x
7=10x-4 /+4
10x=11
x=11/10
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
9x²+6x+1-(x²-6)=16+16x+4x²+4x²-20x
9x²+6x+1-x²+6=16+16x+4x²+4x²-20x
8x²+6x+7=8x²-4x+16
6x+7=-4x+16
10x=9
x=0,9
9x^2 +6x+1-(x^2 - 6)=16+ 16x+4x^2 +4x^2-20
9x^2 +6x+1-x^2+6=16+16x+4x^2 +4x^2-20
8x^2+6x+7=8x^2+16x-4 /-8x^2
6x+7=16x-4 /-6x
7=10x-4 /+4
10x=11
x=11/10